2006
DOI: 10.1111/j.1525-1438.2006.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Large-cell neuroendocrine carcinoma of the cervix associated with cervical-type invasive adenocarcinoma: a report of case and discussion of histogenesis

Abstract: A case of cervical large-cell neuroendocrine carcinoma with mucinous-type cervical adenocarcinoma component adjacent to it is presented, and its histopathogenesis and clinical course are discussed under the light of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It might be assumed that neuroendocrine differentiation is a potential marker for aggressiveness. Recently, more attention has been concentrated on the fact that undifferentiated endometrial carcinomas can possess immunopositive reactions for neuroendocrine markers without typical morphological features of neuroendocrine carcinoma [5,14,17]. Tamura et al showed www.fhc.viamedica.pl positive reactions for neuroendocrine markers at 63% of undifferentiated cancers without typical morphological features [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be assumed that neuroendocrine differentiation is a potential marker for aggressiveness. Recently, more attention has been concentrated on the fact that undifferentiated endometrial carcinomas can possess immunopositive reactions for neuroendocrine markers without typical morphological features of neuroendocrine carcinoma [5,14,17]. Tamura et al showed www.fhc.viamedica.pl positive reactions for neuroendocrine markers at 63% of undifferentiated cancers without typical morphological features [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, articles have been published about the coexistence of undifferentiated cancers, serous and endometrioid, with focal positive immunoreactions for one or more neuroendocrine markers without morphological transformation into neuroendocrine cancer [5,[13][14][15][16][17]. This phenomenon is not well known and needs additional studies.…”
Section: Introductionmentioning
confidence: 99%
“…About 40 cases of LCNEC have been reported and frequently coexist with a non-LCNEC component in the cervix (1,2). Few cervical LCNEC with coexisting invasive cervical adenocarcinoma are described in the literature (1,(3)(4)(5)(6), but because of this association, it has been suggested that LCNEC arises from the neuroendocrine cells present in the cervical adenocarcinoma (2,4,6).…”
mentioning
confidence: 94%
“…It is also known that these NEC frequently coexist with a non‐NEC component in the cervix 3,4 . However, few cervical LCNEC with coexisting invasive cervical adenocarcinoma are described in the literature 2,3,5,6 . Furthermore, to the best of our knowledge, there are no reports describing NEC associated with intestinal variant invasive mucinous adenocarcinoma (INTAD) so far.…”
mentioning
confidence: 99%